Additive Effects of Levodopa and a Neurorestorative Diet in a Mouse Model of Parkinson’s Disease - Perez-Pardo, Paula; Broersen, Laus M.; Kliest, Tessa; van Wijk, Nick; Attali, Amos; Garssen, Johan; Kraneveld, Aletta D. (Frontiers in Aging Neuroscience, 2018)
Though Parkinson’s disease (PD) clinical picture is generally dominated by motor impairment, non-motor symptoms, such as cognitive decline and gastrointestinal dysfunctions, may develop before motor symptoms and have major effects on quality of life. Levodopa is the most commonly used treatment of motor symptoms but has serious side-effects with prolonged use and does not stop the degenerative process. Moreover, gastrointestinal dysfunctions interfere with the absorption of levodopa and modify its effectiveness. Since most patients are on levodopa treatment, there is a need for combinational therapies that allow for an effective reduction of both motor and non-motor symptoms. We have recently shown that a diet containing precursors and cofactors required for membrane phospholipid synthesis, as well as prebiotic fibres, had therapeutic effects in a PD mouse model. We now investigate the effects of combined administration of the same diet together with levodopa in the rotenone model of PD. Mice were injected with rotenone or vehicle in the striatum. The dietary intervention started after full induction of motor symptoms. The effects of dietary intervention and oral treatment with different doses of levodopa were assessed weekly. Motor and cognitive functions were tested, intestinal transit was analysed and histological examination of the brain and the colon was assessed. Our results confirm our previous findings that rotenone-induced motor and non-motor problems were alleviated by the active diet. Levodopa showed an additive beneficial effect on rotarod performance in rotenone-treated animals fed with the active diet. No negative interaction effects were found between the active diet and levodopa. Our findings suggest that the dietary intervention might confer additional clinical benefits on patients receiving levodopa treatment.